A semi-analytical model for heat transfer in coaxial borehole heat exchangers. (January 2021) - Wang, Changlong; Lu, Yuehong; Chen, Lewen; Huang, Zhijia; Fang, Han
Highlights: A model is developed by considering geothermal gradient and borehole heat capacity. The model matches better with experimental data than another model. The model matches well with OGS simulation data of a deep CBHE. The results show that the model is feasible and efficient. Abstract: Heat transfer model is important for the design of coaxial borehole heat exchanger (CBHE). However, the existing models have some disadvantages, such as costing too much computation time, ignoring the geothermal gradient and concerning the borehole heat capacity as a whole. In this paper, a semi-analytical model is developed by considering the geothermal gradient and the heat capacities of different parts of the borehole: 1D radial heat transfer in the grout and the soil is analyzed based on an analytical solution; temperature distributions of the internal fluid and the annular fluid are calculated numerically. To verify the feasibility of the proposed model, it is compared with another model and experimental data, and it is compared with OGS simulation data of a deep CBHE. Compared with another model, the fluid temperature distributions calculated by the proposed model match better with experimental data especially at the early time of heat injection. The fluid temperature distributions calculated by the proposed model match well with OGS simulation data except during the early several days, noting that the OGS simulation data are not accurate at the early time. The results show that the proposed model is feasible and efficient.